Salicylaldehydate coordinated two-dimensional-conjugated metal-organic frameworks - Mohammed, Abdul Khayum; Pena-Sanchez, Pilar; Pandikassala, Ajmal; Gaber, Safa; AlKhoori, Ayesha A.; Skorjanc, Tina; Polychronopoulou, Kyriaki; Kurungot, Sreekumar; Gandara, Felipe; Shetty, Dinesh (Chemical Communications, 2023)
A novel class of copper-based 2D-c-MOF was synthesized from 1,3,5-triformylphloroglucinol using green mechano-chemistry. Herein, metal coordination with the salicylaldehyde functional moiety was explored for the first time in MOFs. Moreover, an intrinsic semiconductive copper-based SA-MOF thin film was fabricated using an in situ salt-free method at room temperature.

Heteroatom-synergistic effect on anchoring polysulfides in chalcone-linked nanographene covalent organic frameworks for high-performance Li―S batteries - Ranjeesh, Kayaramkodath Chandran; Javaregowda, Bharathkumar H.; Gaber, Safa; Bhauriyal, Preeti; Kumar, Sushil; Skorjanc, Tina; Finsgar, Matjaz; Heine, Thomas; Krishnamoorthy, Kothandam; Shetty, Dinesh (Advanced Science, 2025)
Lithium-sulfur (Li & horbar;S) batteries are an attractive option for future energy storage devices because they offer higher theoretical specific capacity, energy density, and cost-effectiveness than commercial lithium-ion batteries. However, the practical applications of Li & horbar;S batteries are significantly limited by the shuttle effect caused by intermediate lithium polysulfides (LiPSs) and slow redox kinetics. In this study, the molecular engineering of chalcone-linked, sp(2)-bonded nanographene-type covalent organic frameworks (COFs) as sulfur hosts is reported to enhance interactions with LiPSs, thereby effectively suppressing the shuttle effect. The developed sulfur-hosting cathode material demonstrated outstanding battery performance, surpassing most reported materials by achieving a specific capacity of 1228 mA h g(-1) at 0.5C, with 80% retention after 500 cycles and an average Coulombic Efficiency (C.E.) of 99%. Additionally, the mechanisms of sulfur immobilization, the subsequent conversion into lithium polysulfides (LiPSs), and their binding energies with COFs are investigated using density functional theory (DFT) calculations. These findings offer valuable insights into the structure-property relationships essential for developing more efficient sulfur-hosting cathodes.
Keywords: anion-pi interaction; covalent organic frameworks; lithium-sulfur battery; nanographene; polysulfide shuttle